PE Wax Microparticle Production by External Mixing Two-Fluid Nozzle Atomization Process - Kulchanat Prasertsit (Science Faculty of Chiang Mai University, 2019)
The effects of atomizing temperature, air pressure and air to liquid diameter ratio on particle size, particle size distribution and shape were studied in a polyethylene wax (PE wax) atomization process in the external mixing two-fluid nozzle atomizer. PE wax was melted and atomized at temperatures ranging from 120˚C to 180˚C, and atomizing air pressure was applied at pressures ranging from 1 to 7 bars. The results indicate that the particle size and bulk density of the PE wax particles decreased as the liquid cap diameter decreased and the air pressure and/or the melting temperature increased. The micrograph from a scanning electron microscope (SEM) showed that the atomization process produced smooth spherical PE wax particles.